Microvessel density in Renal Cell Carcinoma - Habib, Manal A.; Rasheed, Nabeel A.; Ibrahim, Mazin J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Prognostic histological evaluation of many cancers have recently concentrated on angiogenesis. Materials &Methods: A total of twenty formaline-fixed, paraffin embedded blocks of renal cell carcinoma were included in this study. Sections were subjected for immunohistochemical staining of CD34. The median of the MVD of all cases of RCC were obtained to divide the cases into high- and low-MVD score groups and were correlated with the tumor stage and grade. Results: there was a significant correlation of the high MVD score with tumor stage (P=0.02). Conclusion: MVD may be considered as a potential prognostic marker for RCC.